Slamming the Door: Reinventing Kitchen Narratives in Contemporary Indian Movies - Alex, Gigy J.; Justin, Babitha (SARE: Southeast Asian Review of English, 2023)
Abstract In the last ten years, Indian cinema has envisaged culinary spaces as patriarchal structures embedded with the hegemonic practices of the family. Subsequently, Indian cinematic spaces have wielded the kitchens of the Indian subcontinent to interrogate the issues related to gender, identity, culture, and the nation through its visual spaces. The culinary is politicized; the domestic space that has depicted hegemonic masculinity and intersectionality for centuries has been analyzed, exposed, and reimagined in movies like Stanley Ka Dabba (Hindi, 2011), The Lunchbox (Hindi, 2013), Kaaka Muttai (Tamil, 2014), Aamis (Assamese, 2019), and The Great Indian Kitchen (Malayalam, 2021). These movies constantly interrogate and challenge the gender roles and performances prevalent in Indian kitchens. The act of cooking, an agent of a woman's creative expression, has long been understood as an act where food preparations become rituals and performances, and kitchen spaces become a prison house for women. These movies question the power relations which overlay the culinary preparation and consumption in kitchen spaces and thereby mimic the manifestation of gender politics and power play. With the increasing patrilocal families, especially in India, cooking is no more an art or a technique but a bonded labour. This paper investigates the practical ways in which the movies lay bare the issues related to the manifestation of gender identity and the representation of the hegemonic other by reimagining, reinventing and redefining culinary spaces. Keywords: culinary spaces, kitchen, cooking, gender performance, identity contestation, agency